The educational potential of student athletes and their risks in the transition to a second career - Mirontsov, Igor V. (Journal of the Belarusian State University. Sociology, 2020)
This article is about risks associated with the transition to a second career in conditions of incomplete realization of educational potential by athlete-students. Based on the material of an empirical research conducted among Belarusian athletes of international level who finished their sport careers, demonstrates the existing barriers at the level of school, secondary specialized and higher education of young athletes, which make it difficult for them to realize their educational potential. The relevance of this problem is indicated and necessity for elaboration within the framework of the development Strategy for the development of state youth policy of the Republic of Belarus for 2020–2030.
Keywords: education of athletes; youth; specialized secondary education; higher education; social risks; second career